MODEL OF COMMUNITY ECONOMIC DEVELOPMENT THROUGH BUSINESS PARTNERSHIP BASED ON RELIGIOUS AND SOCIAL ORGANIZATION Study at Syirkah Amanah Gas Station, Muhammadiyah Regional Leader of Lumajang - Hakim, Imamul; Sulistianingati, Arini; Syarif, Mohammad (Universitas Muhammadiyah Prof DR HAMKA, 2019)
In developing the economy of the people in the era of globalization with high competitive power requires the right approach. The partnership model is one way to improve community competitiveness, especially in the small business sector. However, in realizing and developing a partnership model, it will be very difficult to apply if it is only carried out by the community independently, especially the lower classes of society. The presence of the Government and third parties is needed in helping to establish partnerships. It is essential to initiate the realization of business partnerships among the community. The role of Religious and Social Organizations as third parties has proven to have a significant contribution in advancing the nation, especially in the fields of education, health, and social assistance. So it is necessary to maximize the role of religious and social organizations in encouraging economic development of the community through coaching and partnerships. Persyarikatan Muhammadiyah, which is engaged in the socio-religious field, has shown its contribution to enlightenment, empowerment, and advancement that provides benefits for the people as a manifestation of the da'wah of Amar Ma'ruf Nahi Mungkar. Syirkah Amanah gas station is one manifestation of Muhammadiyah's involvement in the empowerment and economic development of the community. The purpose of this study was to reveal the partnership model applied by the Muhammadiyah Regional Leader of Lumajang at the Syirkah Amanah Gas Station to be able to find the right and appropriate business partnership model to be implemented in the community. The research approach used in this study is a descriptive qualitative research approach that seeks to explore and find the main objectives of the research. Keywords: Partnership, Community Economic Development, Muhammadiyah